Investigation of Disc Cavity Sealing Efficiency Using CFD - Peruvemba Krishnan, Yogesh (My University, 2025)
The wheelspace cavity between a stator and rotor disc in gas turbines are prone to ingestion of hot gases which threatens the lifetime and safe operation of the turbine. Traditionally, pressurized cooling gas known as, Purge gas, is bled from compressor stage to seal the cavity. The influence of purge - mainstream density ratio (DR), plays a vital role in efficient sealing of the cavity and holds significant practical implications for future engine designers. Building upon prior experimental tests performed at KTH University in collaboration with Siemens Energy AB, the thesis primarily investigates the influence of this DR using CFD simulations. The investigation is carried out at design point of 10540 RPM (Cf = 0.35) for three purge flow rates 0.5%, 1.0%, 1.5% (Φ0 = 0.025, 0.050, 0.075) of main annulus mass flow. The tested purge gases are Air (DR =1) and Argon (DR = 1.38). The simulations are performed in Ansys CFX with increasing modeling complexity starting from steady state RANS to URANS and hybrid RANS- LES model, SBES. Further, a comparison of computational domains, single passage and 51◦ sector domain was also evaluated. The results highlight the importance of sector domain over single passage domain and the need for URANS simulations to capture the unsteady ingress phenomenon. The ingress is evaluated using the non-dimensional variable, Sealing Effectiveness, at various radial locations. Regardless of the purge gas, an improved sealing is observed for increasing purge flow rates and for decreasing radius, as expected. Validation of CFD predictions showed a good agreement for Air (DR =1). While for Argon (DR = 1.38), an increased sealing is predicted directly contradicting experimental conclusion. This discrepancy was attributed to the seed gas concentration level (1% CO2) used in the experiment resulting in overestimation of ingress. For the low purge flow rate Φ0 = 0.025, regardless of purge gas a poor agreement was observed owing to the slow convection rate. While a longer simulation run performed using SBES showed relative improvement, the case still warrants further investigation
Keywords: Gas turbines; Wheelspace cavity; Cavity purge flow; Ingress; CFD; Density ratio; Sealing effectiveness